Model Bait Suci Yerusalem dan Penerapannya dalam Arsitektur Spiritual Rumah Retret Kristen - Stefani Ester Natania; Joseph Christ Santo; Avi Marlina (Angelion, 2025)
This study aims to discuss the model of the Jerusalem Temple in the Old Testament and its relevance to the concept of spiritual architecture in the design of Christian Retreat Houses. The temple itself is understood to be arranged into three areas or space zones, namely the court, the holy room, and the most holy room. When associated with the approach of spiritual architecture, this model reflects the spiritual journey of man from the profane zone to the sacred zone closer to God. The method used is qualitative descriptive qualitative based on literature, by collecting and processing data in the form of Bible, books, and articles to deepen the discussion. Through the study of theological literature and architectural theory, this study examines how aspects of the site, space, ornaments, and furnishings of the Temple can be applied to a Christian Retreat House that is contextual and appropriate today. The results of this study show that the integration between Temple model and spiritual architectural principles can provide a design framework concept for the design of Christian Retreat Houses. The results of this research are expected to contribute to religious architecture in Indonesia, as well as provide a conceptual approach that is in accordance with the teaching of the Christian faith. Penelitian ini bertujuan untuk membahas model Bait Suci Yerusalem dalam Perjanjian Lama dan relevansinya terhadap konsep arsitektur spiritual pada perancangan Rumah Retret Kristen. Bait Suci sendiri dipahami tersusun menjadi tiga area atau zona ruang, yaitu pelataran, ruang kudus, dan ruang maha kudus. Jika dikaitkan dengan pendekatan arsitektur spiritual, model ini mencerminkan perjalanan spiritual manusia dari zona profan menuju ke zona sakral yang lebih dekat dengan Allah. Metode yang digunakan adalah kualitatif deskriptif berdasarkan literatur, dengan mengumpulkan dan mengolah data yang berupa Alkitab, buku, dan artikel untuk memperdalam pembahasan. Melalui kajian literatur teologis dan teori arsitektural, penelitian ini mengkaji bagaimana aspek tapak, ruang, ornamen, dan perabot pada Bait Suci dapat diterapkan ke dalam sebuah Rumah Retret Kristen yang kontekstual dan sesuai pada masa kini. Hasil dari kajian ini menunjukkan integrasi antara model Bait Suci dan prinsip arsitektur spiritual dapat memberikan konsep kerangka desain pada perancangan Rumah Retret Kristen. Hasil dari penelitian ini diharapkan dapat berkontribusi bagi arsitektur religius di Indonesia, sekaligus memberikan pendekatan konseptual yang sesuai dengan pengajaran iman Kristen.